2022
DOI: 10.1021/acsenergylett.2c00865
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Method for Defect Reduction and Improved Performance of p-i-n Vapor-Deposited Perovskite Solar Cells

Abstract: As perovskite-based photovoltaics near commercialization, it is imperative to develop industrial-scale defect-passivation techniques. Vapor deposition is a solvent-free fabrication technique that is widely implemented in industry and can be used to fabricate metal-halide perovskite thin films. We demonstrate markably improved growth and optoelectronic properties for vapor-deposited [CH(NH 2 ) 2 ] 0.83 Cs 0.17 PbI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 60 publications
1
34
0
Order By: Relevance
“…The strongly increasing optical absorption coefficient of FA 0.83 Cs 0.17 PbI 3 as the wavelength is reduced results in the bluer light generating electron−hole pairs very close to the HTL interface in solar cells with a p−i−n architecture. 22 This means holes are more readily extracted due to the short distance to the electrode, whereas electrons have to traverse most of the device depth. The drop in EQE at wavelength <500 nm for solar cells with ZnPc HTLs as compared against those with CuPc HTLs indicates that electrons recombine rapidly at the FA 0.83 Cs 0.17 PbI 3 −ZnPc interface or are extracted into the ZnPc and recombine there.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strongly increasing optical absorption coefficient of FA 0.83 Cs 0.17 PbI 3 as the wavelength is reduced results in the bluer light generating electron−hole pairs very close to the HTL interface in solar cells with a p−i−n architecture. 22 This means holes are more readily extracted due to the short distance to the electrode, whereas electrons have to traverse most of the device depth. The drop in EQE at wavelength <500 nm for solar cells with ZnPc HTLs as compared against those with CuPc HTLs indicates that electrons recombine rapidly at the FA 0.83 Cs 0.17 PbI 3 −ZnPc interface or are extracted into the ZnPc and recombine there.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The strongly increasing optical absorption coefficient of FA 0.83 Cs 0.17 PbI 3 as the wavelength is reduced results in the bluer light generating electron–hole pairs very close to the HTL interface in solar cells with a p–i–n architecture . This means holes are more readily extracted due to the short distance to the electrode, whereas electrons have to traverse most of the device depth.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve this problem, vapor-deposited MA-free perovskite films have been studied. For instance, Lohmann and coworkers showed that partially substituting PbCl 2 for PbI 2 could significantly suppress defects in FA 0.83 Cs 0.17 PbI 3 films [82].…”
Section: D Lead Halide Perovskitesmentioning
confidence: 99%
“…Organic–inorganic halide perovskite solar cells (PSCs) have drawn considerable attention over the past decade because of the remarkable certified power conversion efficiency (PCE) up to 25% for small-area devices. Despite the attractive PCE in small-area devices, the long-term stability of perovskite solar modules (PSMs) still presents many challenges, which are mainly affected by oxygen, moisture, heat, and high-energy irradiation. Thus, the literature reports decelerating the degradation of the perovskite and prolonging the PSC lifetime via the methods of hydrophobic treatment, interfacial modification, and encapsulation. , However, the photostability of the PSMs (especially under UV irradiation), as a nonnegligible point in the practical application process, has rarely been reported. In particular, the strong UV light in the solar spectrum easily destroys the perovskite materials, inducing undesirable vacancies , (V MA or FA , V Pb , and V I ), ion migration, and halide segregation. ,,, Meanwhile, the inevitable defects in the process of large-scale perovskite film fabrication further aggravate the photodegradation of the organic ions (FA + /MA + ) in the PSM.…”
mentioning
confidence: 99%